San Francisco International Airport and Quantum Secure's SAFE for aviation system : making the business case for corporate security security - Diermeier, Daniel; Meagher, Evan ([London] : SAGE, 2016)
In 2008 San Francisco International Airport had announced a plan to renovate and reopen Terminal 2. Assistant deputy director of aviation security Kim Dickie had selected Quantum Secure's SAFE software suite as the new credentialing system, but she needed to develop a business case quickly that would give the green light to the purchase. The case describes a scenario that occurs frequently in the real world, in which a decision offers some real but qualitative value in ways that are difficult or impossible to quantify.
Originally Published in: Diermeier, D., & Meagher, E. (2013). San Francisco International Airport and Quantum Secure's SAFE for Aviation System: Making the Business Case for Corporate Security. 5-312-503. Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on May 4, 2016).
Keywords: elektronické knihy; electronic books; San Francisco International Airport (Calif.); Airports -- Management -- Case studies; Corporations -- Security measures -- Case studies; Information technology -- Management -- Case studies; Accounting -- Case studies